Hepatitis B and C in pregnancy - Seow, H.F. (Churchill Livingstone, 1999)
In general, pregnancy does not influence the course of hepatitis B (HBV) and C (HCV) infection. Most neonates born to mothers who suffer from acute viral hepatitis B and C are asymptomatic. Chronic hepatitis B and C infections can be transmitted to neonates. This route of transmission of HBV is a major contributing factor to the high carrier rate in endemic countries where 80-95% of infants born to HBsAg/HBeAg-positive (hepatitis B surface antigen and hepatitis B e antigen respectively) mothers are infected. Despite the availability of a immunoprophylactic vaccine, 10-15% of these infants are still infected. The possible reasons for vaccine failure include the ability of HBV antigens to induce immunotolerance and the existence of HBV variants. The factors contributing to vertical transmission of HBV and HCV are also discussed. These factors include viral load, virus variants and sensitivity of diagnostic tests. The rate of vertical transmission of HCV of less than 5% is lower compared to HBV in HCV-ribonucleic-acid-positive mothers. However, the risk of HCV transmission is increased to about 23% if the pregnant women are also human immunodeficiency virus (HIV) positive.